Seasonal variability of water quality index in the Hooghly Estuary - Banik, Surajit K.; Suresh, V. R.; Manna, R. K. (Journal of the Inland Fisheries Society of India, 2021)
Health of the Hooghly estuary was estimated through Water Quality Index (WQI) developed using ten water quality parameters, viz., specific conductivity, turbidity, pH, total dissolved solids, dissolved oxygen, biochemical oxygen demand, chloride, total alkalinity, total hardness, and nitrate-N measured at three different stations along the salinity gradient. Weighted arithmetic index method was used for calculation of WQI. For classifying water quality in each of the sampling stations, five-point rating scale was used. Wide fluctuations in monthly WQI were observed in this estuarine zone with the highest values during pre-monsoon month of May and the lowest values during monsoon month of October. From WQI values (mostly >100) throughout the year, it was evident that Hooghly-Bhagirathi estuarine system is unsuitable for drinking and propagation of wildlife and freshwater aqua culture as per water quality standards. It was also observed that there is a severe anthropogenic influence on most of the parameters. Major causes of deterioration in water quality were discharge of untreated industrial and municipal wastes, besides high level of other anthropogenic activities. Key words WQI; Hooghly estuary; India